2000
DOI: 10.1002/1531-8249(200009)48:3<388::aid-ana16>3.3.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Gene polymorphism affecting α1‐antichymotrypsin and interleukin‐1 plasma levels increases Alzheimer's disease risk

Abstract: Plasma levels of alpha1-antichymotrypsin (ACT) and interleukin-1beta (IL-1beta) were increased in patients with probable Alzheimer's disease (AD). A common polymorphism within ACT and IL-1beta genes affected plasma levels of ACT or IL-1beta, and AD patients with the ACT T,T or IL-1beta T,T genotype showed the highest levels of plasma ACT or IL-1beta, respectively. The concomitant presence of the ACT T,T and IL-1beta T,T genotypes increased the risk of AD (odds ratio: 5.606, confidence interval: 1.654-18.996) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 0 publications
1
45
1
Order By: Relevance
“…Student's paired t-test (two-tailed) was used to determine significance only gene region investigated in the AD population. Previous data have shown that the TT genotype of this region increases the risk of developing early sporadic AD and exhibit a trend towards increased plasma ACT levels in AD patients (Licastro et al 2000b). The data reported here confirm and extend those observations by demonstrating a direct functional effect of the promoter mutation.…”
Section: Promoter Regionsupporting
confidence: 90%
See 1 more Smart Citation
“…Student's paired t-test (two-tailed) was used to determine significance only gene region investigated in the AD population. Previous data have shown that the TT genotype of this region increases the risk of developing early sporadic AD and exhibit a trend towards increased plasma ACT levels in AD patients (Licastro et al 2000b). The data reported here confirm and extend those observations by demonstrating a direct functional effect of the promoter mutation.…”
Section: Promoter Regionsupporting
confidence: 90%
“…This may be ascribed to the high frequency of the Apo E4 allele in the AD population, its dominant effect and/or to the multifactorial nature of the disease. Recently, new evidence has been obtained that suggests that ACT and interleukin-1β genotypes, both reflecting increased inflammation, are associated with the risk of developing early-onset sporadic AD independently of Apo E4 status (Licastro et al 2000b).…”
Section: Introductionmentioning
confidence: 99%
“…However, this polymorphism is located within the promoter region and may influence the expression of IL-1A. Similarly to another polymorphism located in the promoter region of the IL-1B gene that has already been associated with increased production of IL-1B [8], the IL-1A allele 2 could confer increased risk for AD by inducing an elevation in IL-1A production, compared with the IL-1A allele 1. It is possible that overexpression of IL-1A and 1B may increase the amount of cytokine-mediated inflammation in the AD brain [16].…”
Section: Discussionmentioning
confidence: 98%
“…In addition, activated microglia, overexpressing IL-1, are intimately associated with neurons bearing successive stages of neurofibrillary tangles [10]. Recent authors [3,5,8,12,14] have reported that genetic variation in genes encoding IL-1A and IL-1B are associated with an increased risk of AD, perhaps through upregulation of the cytokine cascade. One of these polymorphisms is located in the 5' regulatory region of the IL-1A gene (a C-to-T transition at position -889 relative to the start site of transcription), resulting in two alleles, designed allele 1 and allele 2.…”
Section: Introductionmentioning
confidence: 99%
“…The biological significance of the polymorphism in the 5 0 -flanking regulatory region at -889 of the IL1A gene is not completely clarified. However, it has been shown that the IL1A-889 SNP is located within the promoter region and may therefore influence the expression of IL1A, as has been reported for a polymorphism located in the promoter region of the IL1B gene which has been associated to increased production of IL-1b [27]. The IL1A-889 polymorphism has been associated with the risk factor of developing Alzheimer's Disease (AD) [28][29][30][31], supposedly mediated by inflammatory processes.…”
Section: Discussionmentioning
confidence: 99%